Nrf2 as a modulator of oxidative stress - Inam Sameh Arif; Yassir Mustafa Kamal; Israa Burhan Raoof (College of Pharmacy / Mustansiriyah University, 2022)
Nrf2 is active protein presents in the cytoplasm in the cells of the body. In the presence of an activators, Nrf2 can enter the nucleus which bind to Antioxidant Responses Elements (ARE) or otherwise named human ARE (hARE) which control the whole antioxidants activity in human cell. Many factors may contribute to defective or overwhelmed cellular antioxidants activities for instances aging and cellular damages. These cellular damages can be produced by free radicals or oxidative stress. In the mechanism, if Nrf2 activated in the nucleus, can caused the production of collaborative antioxidants enzymes especially: catalase, glutathione (GLT) and superoxide dismutase (SOD) as a responsible for detoxification of free radical inside the cells.